A meta-analysis using individual patient data of trials comparing artemether with quinine in the treatment of severe falciparum malaria. - Artemether-Quinine Meta-analysis Study Group (2001)
We conducted a meta-analysis using individual patient data from randomized controlled trials comparing artemether and quinine in severe falciparum malaria. Eleven trials were identified, of which 8 were clearly randomized. Original individual patient data on 1919 patients were obtained from 7 trials, representing 85% of the patients in the original 11 studies. Overall there were 136 deaths among the 961 patients treated with artemether, compared with 164 in the 958 treated with quinine [14% vs 17%, odds ratio (95% confidence interval) 0.8 (0.62 to 1.02), P = 0.08]. There were no differences between the 2 treatment groups in coma recovery or fever clearance times, or the development of neurological sequelae. However, the combined 'adverse outcome' of either death or neurological sequelae was significantly less common in the artemether group [odds ratio (95% CI) 0.77 (0.62 to 0.96), P = 0.02], and treatment with artemether was associated with significantly faster parasite clearance [hazard ratio (95% CI) 0.62 (0.56 to 0.69), P < 0.001]. In subgroup analyses artemether was associated with a significantly lower mortality than quinine in adults with multisystem failure. In the treatment of severe falciparum malaria artemether is at least as effective as quinine in terms of mortality and superior to quinine in terms of overall serious adverse events. There was no evidence of clinical neurotoxicity or any other major side-effects associated with its use.